2018
DOI: 10.3390/md16060217
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacteria as Nanogold Factories: Chemical and Anti-Myocardial Infarction Properties of Gold Nanoparticles Synthesized by Lyngbya majuscula

Abstract: To the best of our knowledge, cyanobacterial strains from the Arabian Gulf have never been investigated with respect to their potential for nanoparticle production. Lyngbya majuscula was isolated from the AlOqair area, Al-Ahsa Government, Eastern Province, Kingdom of Saudi Arabia. The cyanobacterium was initially incubated with 1500 mg/mL of HAuCl4 for two days. The blue-green strain turned purple, which indicated the intracellular formation of gold nanoparticles. Prolonged incubation for over two months trigg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(34 citation statements)
references
References 62 publications
4
30
0
Order By: Relevance
“…El-Sheekh et al studied the inhibitory activity of Ag-NPs synthesized by S. platensis, Chlorella vulgaris, and Scenedesmus obliquus against Microcystis aeruginosa. 129 M. aeruginosa are well known to be harmful microalgal, which secrete toxins that induce liver cancer. The results of this work encouraged the use of Ag-NPs as antialgal agents to reduce the harmful effect of M. aeruginosa.…”
Section: Antialgal Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…El-Sheekh et al studied the inhibitory activity of Ag-NPs synthesized by S. platensis, Chlorella vulgaris, and Scenedesmus obliquus against Microcystis aeruginosa. 129 M. aeruginosa are well known to be harmful microalgal, which secrete toxins that induce liver cancer. The results of this work encouraged the use of Ag-NPs as antialgal agents to reduce the harmful effect of M. aeruginosa.…”
Section: Antialgal Activitymentioning
confidence: 99%
“…Bakir et al and Younis et al reported that Au-NPs synthesized by L. majuscule have anti-myocardial infarction properties. 129,130 They showed that Au-NPs alone or with cyanobacterial extract inhibit the isoproterenol-induced changes in serum cardiac injury markers, ECG, arterial pressure indices, and antioxidant capabilities of the heart. Also, Ag-NPs synthesized by phycobiliproteins extracted from Nostoc sp.…”
Section: Other Applicationsmentioning
confidence: 99%
“…Meanwhile, microalgae are considered as a promising tool for nanoparticle production due to their high growth rates and high biomass production. Cyanobacteria, such as Gloeocapsa sp., Lyngbya majuscula, Spirulina platensis, and Anabaena variabilis, have been reported for the biosynthesis of intracellular silver, gold, palladium, and platinum nanoparticles (NPs) [7,[13][14][15][16]. Qualities of nanoparticles are strongly correlated to their size where the high surface-to-volume ratio of nanoparticles resulted in tremendous increase in their physical, chemical, and biological properties [17].…”
Section: Introductionmentioning
confidence: 99%
“…and Pseudomonas stutzeri, which were adapted to alkaline conditions, can be used for efficient biosynthesis of AuNPs, which exhibits potential biomedical use (San Diego et al, 2019). AuNPs nanoparticles obtained using Lyngby Majuscule are used to prevent myocardial infarction (Bakir et al, 2018). Marine bacteria Marinobacter algicola formed various types of AuNPs at pH 7.0, at 30 °C in the presence of nitrate reductase, such as spherical, triangular, pentagonal and hexagonal with the average size of 4-168 nm (Gupta & Padmanabhan, 2018).…”
Section: Eco-friendly Synthesis Of Nanoparticles By Bacteriamentioning
confidence: 99%
“…The nanoparticles obtained in this way show better biocompatibility due to the absence of adsorbed toxic substances. Much of the experimental research has been conducted to create diagnostic and therapeutic nanosheets (Barabadi et al, 2017;Bakir et al, 2018;Mohanasrinivasan et al, 2018).…”
Section: Prospects For the Use Of Nanoparticlesmentioning
confidence: 99%